EFFECT LONG-TERM STORAGE OF CRYOPRESERVED BULL SEMEN IN LIQUID NITROGEN ON PARAMETERS OF QUALITY SPERM - Ляшенко, А. О. (Scientific Progress & Innovations, 2013)
The study of performance straight-forward motility and absolute survival rate of thawed sperm bulls of different breeds in long-term storage in the Bank of genetic resources. It is established positive high correlation between the indicators of motility and an absolute survival rate of sperm (r=0,89) (p<0,001). The studies found that the rates of sperm motility and survival of white-headed bull’s ukrainian, lebedinsky, simmental and gray ukrainian breeds were higher than the current standard on average by 15 %.